Income tax law and accounting - Reyes, Virgilio D. ([Place of publication not identified] : publisher not identified], 1998)
This book is a continuous reading material. The provisions of the National Internal Revenue Code are discussed not in the sequence in which they appear in the law in accordance with their materiality and relevance to the particular subject being discussed.
PART I. Income tax patterns -- Chapter 1. Introduction -- Chapter 2. Tax on individuals -- Chapter 3. Tax on estates and trusts -- Chapter 4. Tax on corporations -- Chapter 5. Improperly accumulated earnings tax of corporations -- Chapter 6. Exempt associations -- II. Gross Income -- Chapter 7. Income; Inclusions and exclusions -- Chapter 8. Income from personal services, business, farming, interest and rent and services -- Chapter 9 Fringe benefit: A fringe benefit Tax -- Chapter 10. Sale or exchange of property -- Chapter 11. Sale or exchange of property - capital gains and losses -- Chapter 12. Sale or exchange of property - capital gain tax on real property -- Chapter 13. Sale of exchange of property - capital gain tax on share of stock -- Chapter 14. Dividend income -- Chapter 15. Share in the income of a general professional partnership, estate or trust -- Chapter 16. Income from whatever source Cancellation of Debt; Damage recovery; prizes and awards; Income from illegal sources. -- Chapter 17, Income from whatever source: Bad Debt recovery and tax refund -- Chapter 18. Income from deferred payment sales and long term contracts. -- III. Deductions from Gross Income -- Chapter 19. Deductions in General; Optional Standard and premium payments -- Chapter 20. Business Expenses, In General -- Chapter 21. Interest and taxes -- Chapter 22. Losses -- Chapter 23. Bad debts and depreciation, depletion and pension trust -- Chapter 24 Contribution research and development -- IV. Procedure -- Chapter 25. Taxable income and income tax -- Chapter 26. Tax credit for foreign income tax-- Chapter 27. Filing of income tax return and payment of income tax.
Keywords: INCOME TAX -- PHILIPPINES; ACCOUNTING -- LAW AND LEGISLATION -- PHILIPPINES